2012
DOI: 10.1002/ijc.27958
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to the mediterranean diet and risk of breast cancer in the European prospective investigation into cancer and nutrition cohort study

Abstract: Epidemiological evidence suggests that the Mediterranean diet (MD) could reduce the risk of breast cancer (BC). As evidence from the prospective studies remains scarce and conflicting, we investigated the association between adherence to the MD and risk of BC among 335,062 women recruited from 1992 to 2000, in ten European countries, and followed for 11 years on average. Adherence to the MD was estimated through an adapted relative Mediterranean diet (arMED) score excluding alcohol. Cox proportional hazards re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
196
2
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(208 citation statements)
references
References 41 publications
7
196
2
3
Order By: Relevance
“…27 Since pre-and postmenopausal breast cancers are often considered as different disease entities, separate Cox models were fitted. 28 As data on menopausal status at diagnosis were lacking, age at time of breast cancer diagnosis (50 versus Figure 1. Overview of EPIC-PANACEA (N 5 205,723).…”
Section: Discussionmentioning
confidence: 99%
“…27 Since pre-and postmenopausal breast cancers are often considered as different disease entities, separate Cox models were fitted. 28 As data on menopausal status at diagnosis were lacking, age at time of breast cancer diagnosis (50 versus Figure 1. Overview of EPIC-PANACEA (N 5 205,723).…”
Section: Discussionmentioning
confidence: 99%
“…The updated search from recent years resulted in the identification of eighteen additional prospective studies published up to June 2013 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) . Characteristics of these recent studies are displayed in Table 3.…”
Section: Updated Systematic Review and Meta-analysismentioning
confidence: 99%
“…3), a greater adherence to the Mediterranean diet still determined a significant protection, to a similar extent as the previous meta-analysis (RR 5 0?96; 95 % CI 0?95, 0?97; P , 0?00001), with evidence of significant heterogeneity across the studies (I 2 5 65 %; P , 0?0 0 1). The heterogeneity seems to be determined by the recent studies investigating breast and colorectal cancer (21)(22)(23) . After exclusion of these three studies, the statistical heterogeneity disappeared (I 2 5 36 %; P 5 0?10), with no modification (10) van den Brandt (2011) (11) Literature-based adherence score to the Mediterranean diet Characteristics of the studies included for this analysis are reported in Tables 1 and 2 for men and women, respectively.…”
Section: Updated Systematic Review and Meta-analysismentioning
confidence: 99%
“…A recent study of the California Teachers Cohort identified a plant-based pattern, which was related to a reduction of BC risk (67) . In parallel, increasing evidence is accumulating that adherence to the a priori defined Mediterranean pattern is associated with a decreased BC risk (68)(69)(70) , although results from these studies are not totally consistent, particularly for premenopausal women (70,71) . The dimension reduction techniques used herein were applied to nutrient densities.…”
Section: Discussionmentioning
confidence: 99%
“…TT and PCA provided overall consistent findings in terms of pattern identification and amount of total variability explained. (58,67,70,75) . Indeed, Fung et al found that a prudent dietary pattern was linked with decreased ER − risk (relative risk = 0·62, 95 % CI 0·45, 0·91) (76) .…”
Section: Discussionmentioning
confidence: 99%